Supporting Peer Feedback on Learning Strategies: Effects on Self-Efficacy and Feedback Quality. (November 2021) - Bürgermeister, Anika; Glogger-Frey, Inga; Saalbach, Henrik
The study focused on supporting the distinct processes of assessment and providing feedback within a peer feedback setting in teacher education and investigates the effects on student teachers' self-efficacy and feedback quality in a quasi-experiment. Student teachers ( n = 129) were asked to repeatedly provide peer feedback on learning strategies and were supported by a digital tool. The support was varied: support in assessment (A; realized by rubrics), in formulating the feedback (F; by providing sentence starters), in both components (A+F), or no support (Control). We conducted a 2 × 2 analysis of variance (ANOVA) to measure the effect on feedback quality and 2 × 2×2 mixed ANOVAs to investigate the effects on self-efficacy. Results revealed that student teachers perceived higher self-efficacy regarding assessing learning strategies and giving feedback after repeatedly giving and receiving peer feedback. While supporting feedback-writing (F) was immediately beneficial for students' self-efficacy, the combination (A + F) was most advantageous in the long run. In addition, feedback quality was higher when students were supported in writing the feedback. The findings show that competencies to assess and to give feedback seem to be distinct components that should be fostered individually. The developed support by the digital tool seems to be one beneficial approach here.